Whole-Exome Sequencing Analysis of Human Semen Quality in Russian Multiethnic Population - Kolmykov, Semyon; Vasiliev, Gennady; Osadchuk, Ludmila; Kleschev, Maxim; Osadchuk, Alexander (Frontiers in Genetics, 2021)
Global trend towards the reduction of human spermatogenic function observed in many countries, including Russia, raised the problem of extensive screening and monitoring of male fertility and elucidation of its genetic and ethnic mechanisms. Recently the whole-exome sequencing (WES) was developed as a powerful tool for genetic analysis of complex traits. We present here the first Russian WES study for identification of new genes associated with semen quality. The experimental 3×2 design of the WES study was based on the analysis of 157 samples including three ethnic groups - Slavs (n=59), Buryats (n=49) and Yakuts (n=49), and two different semen quality groups - pathozoospermia (n=95) and normospermia (n=62). Additionally, our WES study group was negative for complete AZF microdeletions of Y-chromosome. The normospermia group included men with normal sperm parameters in accordance with the WHO recommended reference limit. The pathozoospermia group included men with impaired semen quality, namely with any combined parameters of sperm concentration <15 ×106 /ml, and/or progressive motility <32%, and/or normal morphology <4%. The whole-exome sequencing was performed for all 157 samples. Subsequent calling and filtering of variants was carried out according to the GATK Best Practices recommendations. On the genotyping stage, the samples were combined into four cohorts: three sets corresponded to three ethnic groups, and the fourth set contained all the 157 whole-exome samples. Association of the obtained polymorphisms with semen quality parameters was investigated using χ2 test. To prioritize the obtained variants associated with pathozoospermia, their effects were determined using Ensembl Variant Effect Predictor. Moreover, polymorphisms located in genes expressed in the testis were revealed based on the genomic annotation. As a result, the nine potential SNP-markers rs6971091, rs557806, rs610308, rs556052, rs1289658, rs278981, rs1129172, rs12268007 and rs17228441 were selected for subsequent verification on our previously collected population sample (about 1,500 males). The selected variants located in seven genes FAM71F1, PPP1R15A, TRIM45, PRAME, RBM47, WDFY4 and FSIP2 that are expressed in the testis and play an important role in cell proliferation, meiosis and apoptosis.